End-User Acceptance Of E-Government Services In an Indonesia Regency - Deden Witarsyah; Mohd Farhan MD Fudzee; Mohamad Aizi Bin Salamat (IAES Indonesia Section, 2015)
The aim of this research to investigate citizen’s behaviour in e-Government adoption. The final purpose is tounderstanding of the public intention at the local governmentlevel, the of important things to make e-government servicebecome successful is public acceptance and willingness to use egovernmentservices. Therefore this study used a model ofUTAUT base on the unique problems which consists of six mainvariables that affect behavioral intention and use behavior, thesevariables are privacy, trust, performance expectancy, effortexpectancy, social influence, and facilitating condition. At thepractical level, the research aim to guide e-Government policydecision makers to better plan, design and implemet policies andstrategies.